The study of microheterogeneous distribution of admixture in silicon monocrystals - Червоный, Иван Федорович; Головко, Ольга Петровна (Eastern-European Journal of Enterprise Technologies, 2015)
We have analyzed the accumulation of admixture in the melt at the crystallization frontline in the process of growing silicon monocrystals and studied the model of accelerated crystallization of the melt area. The applied model of the admixture redistribution is as follows: when one layer of silicon crystallizes, one part of the admixture is absorbed by a growing crystal, while the other part remains in the melt and enriches its frontal area. When the second layer of silicon crystallizes, the growing crystal adsorbs the admixture from the admixture-enriched melt after crystallization of the first atomic layer, etc. Therefore, the melt frontal area experiences a stepwise accumulation of admixture and forms an area of the concentrate overcooling, which involves a possible growth of the concentrate to the critical value––there may occur an independent second phase. According to calculations of the equation, the growth rate increases 5 ... 7 times, which provides conditions for a saltatory change in the growth rate and crystallization of the admixture-enriched melt layer. After the saltatory crystallization, the frontline field repeats the admixture accumulation to a certain value and the mode of accelerated crystallization. The strata characteristics can be eliminated or considerably reduced due to the proposed modes of growing single crystals at high velocities. The proposed technology prevents admixture accumulation at the crystallization frontline, and ensures its uniform distribution over a single crystal.